Clinical Efficacy of Acupuncture Combined With Conventional Therapy for C5 Nerve Root Palsy After Posterior Cervical Decompression Surgery: A Randomized Controlled Study - Hua Wei; Qingfeng Shen; Yuang Fu; Yubo Tan; Junwei Gao; Yingpeng Xia (Pain Research and Management)
Trial Registration: Clinical Trial Registry identifier: ChiCTR2300073583